Chinese International Secondary Students’ Experiences with Racism: “It Was the Same Before and After COVID… It Was Just Something Really Normal.” - Liu, Helen; Desai-Trilokekar, Roopa (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2025)
The number of international students enrolled in Canadian K-12 schools has grown tremendously, but there remains limited research available that provides insights into the unique perspectives and challenges of this population. Through in-depth interviews with five Chinese international secondary school students and using Critical Race Theory (CRT), neo-racism and Asian Critical Theory (AsianCrit), this study identifies four key themes that help explore their experiences during the COVID-19 period with anti-Asian sentiments and racism in GTA schools. The article highlights both the strengths and limitations of CRT and AsianCrit and the contributions of Neo-racism in fully accounting for the racist experiences of Chinese international secondary students. It suggests the importance of exploring newer frames such as neo-racism, but also co-ethnic racism and new geopolitics to analyze what shapes and defines international students’ experiences. Finally, the article stresses the need for K-12 schools to confront their problematic institutional cultures and make a sincere and concerted effort to establish an inclusive and supportive environment for international students.